2012
DOI: 10.1089/rej.2012.1329
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Renal Function and Physical Performance in Elderly Hospitalized Patients

Abstract: Chronic kidney disease (CKD) is increasingly recognized as a cause of worsening physical functioning in older patients. The Short Physical Performance Battery (SPPB) is highly reliable in older populations, but no data on older hospitalized patients with different degrees of kidney function are available. We aimed at testing the association between estimated glomerular filtration rate (eGFR) and SPPB, either global score (range 0-12) or its individual components (muscle strength, balance, and walking speed, ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 60 publications
(76 reference statements)
1
41
0
1
Order By: Relevance
“…A greater risk of having a frailty phenotype was observed in another cohort of patients with CKD in more advanced stages of the disease; this phenotype was associated with a 2.5-fold greater risk of death and with the need to start dialysis [30]. The association of CKD with a higher risk of developing limitations in the physical domain of frailty has also been shown in reports focused on exercise capacity and physical functioning [31,32]. Although frailty was not the focus of the present study, the beneficial effects in several markers of physical functioning provided by the home-based exercise give insights into the potential of such interventions for frailty-related physical disturbances.…”
Section: Discussionmentioning
confidence: 64%
“…A greater risk of having a frailty phenotype was observed in another cohort of patients with CKD in more advanced stages of the disease; this phenotype was associated with a 2.5-fold greater risk of death and with the need to start dialysis [30]. The association of CKD with a higher risk of developing limitations in the physical domain of frailty has also been shown in reports focused on exercise capacity and physical functioning [31,32]. Although frailty was not the focus of the present study, the beneficial effects in several markers of physical functioning provided by the home-based exercise give insights into the potential of such interventions for frailty-related physical disturbances.…”
Section: Discussionmentioning
confidence: 64%
“…Moreover, lower physical activity is getting recognized as a risk factor for mortality in these patients, and deeply associated with poor outcomes [18]. Although there have been reported a limited number of study to access the direct association, some studies showed exercise training contribute shortening hospitalization [19,20] and longer survival [21] with better physical functions. We believe that exercises should be an effective treatment to improve survival in CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recent estimates suggest individuals with CKD stage 3b have a threefold increased risk of developing dependence in daily activities such as bathing, dressing, and personal care compared to individuals without renal impairment 16 . Furthermore, there appears to be a faster rate of functional decline 17 . However, studies in the dialysis population are limited to small single center studies of older patients with little information on the difficulties that younger individuals report 15, 16 .…”
Section: Introductionmentioning
confidence: 99%